Wavelike propagation of quorum activation through a spatially distributed bacterial population under natural regulation. (11th June 2021) - Patel, Keval; Rodriguez, Coralis; Stabb, Eric V; Hagen, Stephen J
Abstract: Many bacteria communicate using diffusible pheromone signals known as autoinducers. When the autoinducer concentration reaches a threshold, which requires a minimum population density or 'quorum', the bacteria activate specific gene regulatory pathways. Simple diffusion of autoinducer can activate quorum-dependent pathways in cells that are located at substantial distances from the secreting source. However, modeling has predicted that autoinducer diffusion, coupled with positive feedback regulation in autoinducer synthesis, could also allow a quorum-regulated behavior to spread more rapidly through a population by moving as a self-sustaining front at constant speed. Here we show that such propagation can occur in a population of bacteria whose quorum pathway operates under its own natural regulation. We find that in unstirred populations of Vibrio fischeri, introduction of autoinducer at one location triggers a wavelike traveling front of natural bioluminescence. The front moves with a well-defined speed ∼2.5 mm h −1, eventually outrunning the slower diffusional spreading of the initial stimulus. Consistent with predictions from modeling, the wave travels until late in growth, when population-wide activation occurs due to basal autoinducer production. Subsequent rounds of waves, including waves propagating in the reverse direction, can also be observed late in the growth of V . fischeri under natural regulation. Using an engineered, lac -dependent strain, we show that local stimuli other than autoinducers can also elicit a self-sustaining, propagating response. Our data show that the wavelike dynamics predicted by simple mathematical models of quorum signaling are readily detected in bacterial populations functioning under their own natural regulation, and that other, more complex traveling phenomena are also present. Because a traveling wave can substantially increase the efficiency of intercellular communication over macroscopic distances, our data indicate that very efficient modes of communication over distance are available to unmixed populations of V . fischeri and other microbes.